The mostly true adventures of homer P. Figg - Philbrick, Rodman (Scholastic INC, 2009)
In this award-winning page-turner, twelve-year-old orphan homer runs away from pine swamp, maine, to find his older brother who has been sold into the Union Army. With laugh-aloud humor, homer outwits and ourtruns a colorful assortment of civil war-era thieves, scallywags, and spies as he makes his way south, following clues that finally lead him to gettysburg. Even through a hail of gunfire, homer never loses heart-but will he find his brother? Or will it be too late?